2012
DOI: 10.1152/jn.00756.2011
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of vision, proprioception, and efference copy in storing a neural representation for guiding trail leg trajectory over an obstacle

Abstract: Stepping over obstacles requires vision to guide the leading leg, but direct visual information is not available to guide the trailing leg. The neural mechanisms for establishing a stored obstacle representation and thus facilitating the trail leg trajectory in humans are unknown. Twenty-four subjects participated in one of three experiments, which were designed to investigate the contribution of visual, proprioceptive, and efference copy signals. Subjects stepped over an obstacle with their lead leg, stopped,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…Visual feedback guides motor planning via posterior parietal cortex [50,51]. These processes generate muscular pattern separately from that of locomotion.…”
Section: The Supraspinal Control Of the Cpgmentioning
confidence: 99%
“…Visual feedback guides motor planning via posterior parietal cortex [50,51]. These processes generate muscular pattern separately from that of locomotion.…”
Section: The Supraspinal Control Of the Cpgmentioning
confidence: 99%
“…Skilled locomotor control, such as that exemplified by the precise control of foot trajectory over an obstacle, requires effective sensorimotor integration of visual and proprioceptive input along with information about motor commands (efference copy) (Marigold 2008;Andujar et al 2010;Marigold et al 2011;Lajoie et al 2012). Previous studies have shown that even if online visual cues are obstructed during obstacle crossing (e.g.…”
mentioning
confidence: 99%
“…On the other hand, voluntary control of stepping patterns can become more automatic with practice (e.g., line dancing). Locomotor skills can be learned via visual cues from the environment or proprioceptive cues from the limbs during obstacle avoidance tasks (Erni and Dietz 2001;Lajoie et al 2012). Moreover, there is some evidence that visual cue training could improve gait patterns that transfer to walking without cues in people with Parkinson's disease (Spaulding et al 2013).…”
mentioning
confidence: 99%